(untitled) (International Journal of Engineering and Computer Science, 2017)
In Today’s scenario, files are not secure. They are fetch by any means of attack by eavesdropper like cracking the pins, crashing the OS by viruses, malwares, and plenty of ways. We today can’t sure that files protection wizards are secure and data can’t be reached to the attacker. But if files are encrypted then even files are accessed original data remains confidential. Therefore, this paper represents the File Encryption System based on Symmetric Key Cryptography. I proposed the strategy to encrypt the files/even multiple files can be encrypted by compressing the files into one ‘rar’ file and it uses Blowfish as encryption/decryption standard and Cipher Block Chain Mode to perform the operations. I implemented compression function for 64-bit Initialization Vector(IV), use CBC mode with Blowfish and RC4 for 256-bit keystream. It is more efficient and secure then other general encryption process